Place and non-place:: A STUDY OF THE PERNAMBUCO SCHOOL CURRICULUM AND OF A GEOGRAPHY TEXTBOOK FOR THE 6TH GRADE OF ELEMENTARY SCHOOL (Élisée - Revista de Geografia da UEG, 2022)
This article presents a research aimed at analyzing how the concept of place and non-place is addressed in the Geography School Curriculum of Pernambuco State for Elementary School, along with the analyses of a 6th grade textbook. This research problematizes the approach of place, as a category of analysis of the geographic space, as well as the contribution of humanistic and cultural Geography to the understanding of the debate about place and non-place. This is a qualitative research, of exploratory and descriptive approach, developed through bibliographical revision and documental analysis. For data analysis, we applied Content Analysis, proposed by Bardin (2010). We found that, in the organizer of Geography school curriculum of the 6th grade of primary schools, the place is explicitly mentioned in the first thematic unit, not being mentioned afterwards in the other units, nor in the objects of knowledge and skills. Thus, it does not make explicit the importance of addressing it as a category of analysis, which permeates the other thematic units. About the textbook analysis, we observed that the place, as a category of analysis, is present in only one of the units and even there the figurative representations do not contemplate the perception of place as a lived space. We consider that the contents expressed in the textbook are portraying, most of the times, other countries and concentrates realities of the Brazilian center-south, which characterizes a limitation for the students of the north-northeast. We emphasize that the teacher can remake the contents, considering the place as an element of pedagogical mediation, oriented towards its meaning.
Keywords: Place; Geography; School Curriculum; Didactic Book; Elementary School